LEGAL FOUNDATIONS OF RELIGIOUS TOLERANCE IN THE REPUBLIC OF UZBEKISTAN - Yusupov Azamjon Abdullajanovich (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the legal foundations of religious tolerance in Uzbekistan by examining the constitutional provisions, legislative frameworks, and policy measures that regulate religious freedom while maintaining national security and social stability. Method: A qualitative research approach is employed, utilizing legal analysis, historical records, and policy documentation to evaluate the effectiveness of Uzbekistan’s legal mechanisms in fostering religious tolerance. Comparative analysis with international agreements and best practices further contextualizes the findings. Results: The findings reveal that Uzbekistan has institutionalized religious freedom through constitutional protections, legal regulations, and state oversight. The government has implemented policies that balance religious tolerance with measures to prevent extremism and maintain social order. Interfaith dialogue programs and educational initiatives have also played a crucial role in sustaining religious harmony. Novelty: This study contributes to the discourse on religion and law by demonstrating how Uzbekistan’s legal framework integrates religious freedom with state supervision to ensure national unity. Unlike previous studies that focus solely on religious freedom or security concerns, this research highlights a structured approach that other multicultural societies can adopt to promote religious tolerance while safeguarding social stability.